Pemeriksaan Status Gizi Santri Sebagai Upaya Skrining dan Pencegahan Penyakit Infeksi - Nawawi, Rizki Andini; Amalia, Ella; Sabrina, Tia; Rivani, Erizka; Zanaria, Rima; Diba, Masayu Farah; Usman, Doni; Al-Fayed, Muhammad Sadad; Zefianto, Zefianto; Ansyori, Achmad Rifky; Mansur, M. Syafi'i (Abdimas Universal, 2025)
Nutrition is a contributing factor in the maintenance of optimal immune system functions. Disturbances in nutritional status, such as malnutrition, would impact various structures, mediators, and processes in the immune system in responding to pathogenic infections, hence increasing vulnerability to infections. Adolescents are an age group often considered “healthy”, but screening in this age group proves important in reassuring optimal growth and development, which in turn will also impact the next generation. Pesantren is an Indonesian educational institution serving adolescents with a boarding school system, so it is of high importance for adolescent santri to know their own nutritional status in preventing infectious diseases. This community service event was held at Pesantren Thawalib Sriwijaya to inform about the importance of nutritional status in prevention of infectious diseases. The activities comprised of classical counseling and anthropometric measurement of participating santri. There were 42 participating santri attending Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA) in this event, and plotting results showed most santri had normal nutritional status. However, nutritional status monitoring and awareness to infectious disease still needs to be kept up, as there are various other factors that may influence the spread of various infectious diseases.